If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6p-6=-6(1-6p)
We move all terms to the left:
6p-6-(-6(1-6p))=0
We add all the numbers together, and all the variables
6p-(-6(-6p+1))-6=0
We calculate terms in parentheses: -(-6(-6p+1)), so:We get rid of parentheses
-6(-6p+1)
We multiply parentheses
36p-6
Back to the equation:
-(36p-6)
6p-36p+6-6=0
We add all the numbers together, and all the variables
-30p=0
p=0/-30
p=0
| 6x+3x-2x+5x+7x=57 | | -2x+-1=-11 | | -122=7x-4(8x-7) | | 67=b+3 | | 2x-12-9x=9 | | 49=9+5u | | 2c+30-4=6-4 | | (n-15)*(-5)=-95 | | -2+-4x=18 | | 9/4x-5/4x+1/4x=10 | | 37t=34151 | | 2c+30-4=9-4 | | 3.7t=34151 | | -122=7x-4(8x-7 | | 2c+30-4=8-4 | | (n-15)*(-6)=150 | | F(x)10x^2+F(x)=F(x)7x | | 3x+2+5x=8(x-1) | | k-10=22 | | 40=4x+15+180 | | -2x×358=-2000 | | 2,8=u/2 | | -70-10=x+3x | | 5-6x+5x=-7 | | 1/6.s=4 | | 9=-2x-4 | | 5x-4=3x+14 | | 78=w+29 | | 3(k-1)=-3(k+1) | | g-3=40 | | 2/3-1/5x=-1 | | 0.5x-2.5=77.5+0.3x |